2019
DOI: 10.3390/en12030494
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of a Small-Scale Biomass-to-Energy BFB Gasification-Based System

Abstract: In order to limit global warming to around 1.5–2.0 °C by the end of the 21st century, there is the need to drastically limit the emissions of CO2. This goal can be pursued by promoting the diffusion of advanced technologies for power generation from renewable energy sources. In this field, biomass can play a very important role since, differently from solar and wind, it can be considered a programmable source. This paper reports a techno-economic analysis on the possible commercial application of gasification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 40 publications
2
33
1
Order By: Relevance
“…The expenditures also include the Cc and C O&M . C c is divided into three categories: hardware price ( Cg ), installation cost (25% of C g ) and engineering costs, the engineering costs includes engineering and design (13% of C g ), purchasing & construction (14% of C g ), fuel handling/preparation (9% of C g ) and electrical/balance of plant (6% of C g ) (Porcu et al 2019;Sara et al 2016). C g is the overall price of gasifier system on the basis of various capacities.…”
Section: Techno-economic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The expenditures also include the Cc and C O&M . C c is divided into three categories: hardware price ( Cg ), installation cost (25% of C g ) and engineering costs, the engineering costs includes engineering and design (13% of C g ), purchasing & construction (14% of C g ), fuel handling/preparation (9% of C g ) and electrical/balance of plant (6% of C g ) (Porcu et al 2019;Sara et al 2016). C g is the overall price of gasifier system on the basis of various capacities.…”
Section: Techno-economic Assessmentmentioning
confidence: 99%
“…2) The whole yearly C O&M can be determined by the sum of the costs for the maintenance cost (2% of Cc ), insurance and tax (2% of Cc ), waste disposal (15% of Cc ), electricity cost, liquid fuel cost and personnel cost. Electricity costs are calculated based on electricity consumers and liquid fuel costs are estimated for fuel consumers with 7000 h/year of plant availability (Porcu et al 2019;Sara et al 2016). The unitary cost of electrical and fuel energies supplied in Iceland are equal to 0.03 $/kWh and 1.08 $/lit (0.91 €/$ as conversion rate) (Safarian and Unnthorsson 2018).…”
Section: Techno-economic Assessmentmentioning
confidence: 99%
“…The water/moisture content is important in terms of thermal valorization and conversion efficiency of burnt material, high water content lowers the calorific value [39]. The high moisture content and relatively high carbon value, and an increase of other volatile matter compared to the total composition, make the samples a good candidate for oxidation and gasification processes and have a positive impact on biomass reactivity, ultimately [40]. For proximate analysis, residue of each sample burnt was determined as the ash, and carbon content was estimated [41].…”
Section: Discussionmentioning
confidence: 99%
“…Performance analysis of biomass gasification systems has been studied in many researches [17][18][19][20][21][22][23][24][25][26][27][28]. However, the authors are not aware of any reported paper about the modeling of integrated downdraft biomass gasification with a power production unit.…”
Section: Introductionmentioning
confidence: 99%